Debate: Could the litchi pericarp oligomeric procyanidins bioconverted by Lactobacillus plantarum increase the inhibitory capacity on advanced glycation end products? - Feng, Nianjie; Tang, Fei; Hu, Chuanqin; Cheng, Lei; Lv, Zhejuan; Shen, Yang; Li, Wei; Xiao, Gengsheng; Dong, Hao; Wu, Qian (Frontiers in Nutrition, 2022)
Lactic acid bacteria (LAB) have already been used as fermentation strains to enhance the antioxidant capacity of polyphenols. Antioxidant capacity is one of the most important factors to inhibit advanced glycation end products (AGEs) formation and could LAB increase the inhibitory capacity of procyanidins on AGEs formation? It was surprising that opposite results were obtained both in simulated food processing and gastrointestinal digestion systems. After incubation with Lactobacillus plantarum (L. plantarum), litchi pericarp oligomeric procyanidins (LPOPCs) were bioconverted to several phenolic acids which increased the antioxidant activity as expected. However, antiglycation ability and trapping carbonyl compounds capacity both weakened and it might be the primary reason of decreasing the inhibitory effect on AGEs formation. What’s more, it was found that LPOPCs incubated with L. plantarum inhibited the activity of digestive enzymes and thus decreased the digestibility of glycated protein. Our study systematically proposed for the first time that procyanidins bioconversion is an effective means to improve the antioxidant activity but no remarkable promoting effect on AGEs inhibition.